Design and synthesis of novel 4-substituted 1,4-dihydropyridine derivatives as hypotensive agents - Prasanna A. Datar; Pratibha B. Auti (Journal of Saudi Chemical Society)
Calcium-channel blockers have an important role in the treatment of several cardiovascular disorders. Derivatives of 1,4-dihydropyridines are one of the most potent calcium antagonists. In this study a series of novel 1,4-dihydropyridine calcium channel blockers of general formula diethyl 4-(4-substituted phenyl)-1,4-dihydro-2,6-dimethylpyridine-3,5-dicarboxylate were synthesized and tested for hypotensive activity, including electrocardiographic and effect on heart rate. Compound diethyl 4-(4-benzyloxy phenyl)-1,4-dihydro-2,6-dimethylpyridine-3,5-dicarboxylate (DHP I) and diethyl 4-(2-(2-chlorobenzyloxy) phenyl)-1,4-dihydro-2,6-dimethylpyridine-3,5-dicarboxylate (DHP III), were the most potent in this series. All synthesized compounds lowered rat blood pressure significantly in comparison with DMSO as control and nifedipine was used as positive control.